2011
DOI: 10.4103/0972-0707.85813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage environment on the bond strength of reattachment of crown fragments to fractured teeth

Abstract: Aim:The aim of this study was to examine various storage environments for storing fragments before being bonded to the remaining teeth and also estimate the required force to fracture the restored teeth.Materials and Methods:Sixty mandibular incisor teeth were fractured on the incisal one-third and were divided into five groups of 12 each to be stored in normal saline, water, milk, saliva and dry environments for 24 hours. All the fractured parts in each group were bonded to their relevant apical parts by an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 15 publications
6
35
0
5
Order By: Relevance
“…However, when the fragment was dehydrated for a period of 30 minute or less, rehydration with distilled water 30 min before reattachment can promote recovery of part of the BS . Using the same rehydration time (24 hour) for all groups analyzed, the Shirani et al study showed that teeth with the highest BS values were those that used milk (374.20 N) or saliva (328.6 N) as a moisturizing solution for the dental fragment, whereas a later Sharmin et al study showed that the group presenting the highest BS values was rehydrated in saline for a period of 24 h (75.91 N).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the fragment was dehydrated for a period of 30 minute or less, rehydration with distilled water 30 min before reattachment can promote recovery of part of the BS . Using the same rehydration time (24 hour) for all groups analyzed, the Shirani et al study showed that teeth with the highest BS values were those that used milk (374.20 N) or saliva (328.6 N) as a moisturizing solution for the dental fragment, whereas a later Sharmin et al study showed that the group presenting the highest BS values was rehydrated in saline for a period of 24 h (75.91 N).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, some of them did not make it clear whether the chosen teeth had similar dimensions in relation to such variables as size of the outer crown, pulp size and thickness of the dental tissues, factors which could lead to risk of bias. Although trauma is more frequent in upper anterior teeth, some studies have chosen to use only lower anterior teeth, as they were easier to obtain due to periodontal diseases …”
Section: Discussionmentioning
confidence: 99%
“…Transport the fragment in an appropriate solution: Hank's Balanced Solution (HBSS), milk, egg white, hypertonic dextrose solution or saliva, water [4][5][6][7][8]. If these solutions are not available, store the fragment in the patient's saliva [17]. Pulpal protection is paramount in these acute traumatic situations.…”
Section: Discussionmentioning
confidence: 99%
“…Storing the fragment in storage media increases the bond strength and fracture resistance by preventing dehydration and dimensional changes 8,9,10 . It also improves esthetics 11 .…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Calcium and phosphate are the main elements found in milk and these can stiffen and harden both demineralized and healthy dentin. This may be the reason behind enhancement of bond strength of fragments stored in milk 8 .…”
mentioning
confidence: 99%